INVESTOR REACTION TO THE ANNOUNCEMENT OF FIRST COVID-19 VACCINATION IN INDONESIA - Sutanto, Shieren Amelia; Dermawan, Elizabeth Sugiarto (Graduate Program of Universitas Tarumanagara, 2023)
The COVID-19 pandemic has had a huge impact around the world and presents unprecedented challenges to the health sector. Vaccination programme is a solution to suppress the spread of COVID-19. The purpose was to explain the reaction of the capital market to the announcement of the first COVID-19 vaccination in Indonesia by focusing the differences in abnormal return and trading volume activity before and after the event of vaccination programme. The research method used is quantitative method by secondary data analysis with event study. The event date in this research was January 13rd, 2021 when Indonesia began its nationwide COVID-19 vaccination programme. This event study took a sample of 17 companies in healthcare sector listed on Indonesia Stock Exchange. The event period used was 14 days, 7 days before and 7 days after the announcement of the first COVID-19 vaccination in Indonesia. This research uses descriptive statistical techniques, normality test (one-sample kolmogorov-smirnov test), and paired sample t-test. The results of the paired sample t-test show that there is a significant difference between the abnormal return before and after the announcement of the first COVID-19 vaccination in Indonesia. However, there is no significant difference of trading volume before and after the announcement of the first COVID-19 vaccination in Indonesia.